2010
DOI: 10.1002/fuce.201000029
|View full text |Cite
|
Sign up to set email alerts
|

Pseudocapacitive Properties of Nano‐structured Anhydrous Ruthenium Oxide Thin Film Prepared by Electrostatic Spray Deposition and Electrochemical Lithiation/Delithiation

Abstract: Nano‐structured anhydrous ruthenium oxide (RuO2) thin films were prepared using an electrostatic spray deposition (ESD) technique followed by electrochemical lithiation and delithiation. During the electrochemical lithiation process, RuO2 decomposed to nano‐structured metallic ruthenium Ru with the concomitant formation of Li2O. Nano‐structured RuO2 was formed upon subsequent electrochemical extraction of Li from the Ru/Li2O nanocomposite. Electrochemical lithiation/deliathiation at different charge/discharge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In order to obtain mesoporous hydrous RuO 2 thin films with organized and accessible porosity, Sassoye and workers used ruthenium‐peroxo‐based sols formed with amphiphilic polystyrene‐polyethylene oxide block copolymers as micelle templates that displayed high gravimetric capacitances . Furthermore, to control the porous morphology of electrostatically‐spray‐deposited anhydrous RuO 2 , electrochemical lithiation and delithiation was executed with improved outcome …”
Section: Strategies For Improving Electrochemical Signatures In Ruo2 mentioning
confidence: 99%
“…In order to obtain mesoporous hydrous RuO 2 thin films with organized and accessible porosity, Sassoye and workers used ruthenium‐peroxo‐based sols formed with amphiphilic polystyrene‐polyethylene oxide block copolymers as micelle templates that displayed high gravimetric capacitances . Furthermore, to control the porous morphology of electrostatically‐spray‐deposited anhydrous RuO 2 , electrochemical lithiation and delithiation was executed with improved outcome …”
Section: Strategies For Improving Electrochemical Signatures In Ruo2 mentioning
confidence: 99%
“…Hydrous RuO 2 · x H 2 O and anhydrous RuO 2 were successfully prepared by the ESD technique, with specific capacitances of 650 F g −1 and 500 F g −1 , respectively, at a scan rate of 20 mV s −1 . The capacitance of the anhydrous RuO 2 can be further improved by ESD followed by electrochemical lithiation and delithiation . Based on the reversible conversion reaction, the as‐prepared ESD RuO 2 with primary particle sizes of 15–30 nm will be converted to nanostructured RuO 2 ranging from 2 to 5 nm.…”
Section: Electrode Materials For Supercapacitors Prepared By Esdmentioning
confidence: 99%
“…The capacitance of the anhydrous RuO 2 can be further improved by ESD followed by electrochemical lithiation and delithiation. [174] Based on the reversible conversion reaction, the as-prepared ESD RuO 2 with primary particle sizes of 15-30 nm will be converted to nanostructured RuO 2 ranging from 2 to 5 nm. The specific capacitance will be increased to 653 F g −1 at 20 mV s −1 .…”
Section: Pseudocapacitor Materials Prepared By Esdmentioning
confidence: 99%
“…Furthermore, the ESD technique provides the possibility for the preparation of various anodes without the use of extra binder and conductive materials. 58,124,[145][146][147] It has been demonstrated that the ESD technique shows promising application in LIBs.…”
Section: Electrostatic Spray Deposition (Esd) Techniquementioning
confidence: 99%